Type 4 Dual Left Anterior Descending Artery: A Very Rare Coronary Anomaly Circulation - Marcos Danillo Peixoto Oliveira; Pedro H. M. Craveiro de Melo; Antonio Esteves Filho; Luiz J. Kajita; Expedito E. Ribeiro; Pedro Alves Lemos (Case Reports in Cardiology)
Coronary artery anomalies are congenital changes in their origin, course, and/or structure. They are the second most frequent cause of sudden death in young athletes. Dual LAD artery is a rare coronary anomaly. We present the case of a 44-year-old man with recent onset exertional angina and documented ischemia whose coronary angiogram and computed tomography (CT) showed type 4 dual LAD artery, the rarest and most interesting variant.